1994
DOI: 10.1152/jappl.1994.77.3.1122
|View full text |Cite
|
Sign up to set email alerts
|

Strength training increases insulin action in healthy 50- to 65-yr-old men

Abstract: The insulin resistance associated with aging may be due, in part, to reduced levels of physical activity in the elderly. We hypothesized that strength training increases insulin action in older individuals. To test this hypothesis, 11 healthy men 50-63 yr old [mean 58 +/- 1 (SE) yr] underwent a two-step hyperinsulinemic-euglycemic glucose clamp with concurrent indirect calorimetry and an oral glucose tolerance test (OGTT) before and after 16 wk of strength training. The training program increased overall stren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
131
4
12

Year Published

2001
2001
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 229 publications
(167 citation statements)
references
References 0 publications
20
131
4
12
Order By: Relevance
“…In addition, the changes in central adiposity in the progressive resistance training group were associated with increases in strength, while in the control group alone strength change was not a significant predictive factor for the change in waist circumference. Adult studies have found that resistance training improves muscle mass, strength and insulin sensitivity 56,57 and decreases visceral fat 5-7 although it is not clear whether these linked benefits are due to changes in energy expenditure (resting metabolic rate and physical activityrelated expenditure), muscle metabolism, insulin regulation, counter-regulatory hormones or adipokines induced by exercise. [58][59][60] In our short-term study, we did not hypothesize that fat-free mass would improve significantly or underlie the changes in fat mass or associated metabolic benefits, but in longer term progressive resistance training interventions in children it would be important to measure all body composition adaptations (muscle, bone, fat) to ascertain the relationships between adaptations in these body tissues during maturation.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the changes in central adiposity in the progressive resistance training group were associated with increases in strength, while in the control group alone strength change was not a significant predictive factor for the change in waist circumference. Adult studies have found that resistance training improves muscle mass, strength and insulin sensitivity 56,57 and decreases visceral fat 5-7 although it is not clear whether these linked benefits are due to changes in energy expenditure (resting metabolic rate and physical activityrelated expenditure), muscle metabolism, insulin regulation, counter-regulatory hormones or adipokines induced by exercise. [58][59][60] In our short-term study, we did not hypothesize that fat-free mass would improve significantly or underlie the changes in fat mass or associated metabolic benefits, but in longer term progressive resistance training interventions in children it would be important to measure all body composition adaptations (muscle, bone, fat) to ascertain the relationships between adaptations in these body tissues during maturation.…”
Section: Discussionmentioning
confidence: 99%
“…Those randomised to aerobic and resistance exercise combined performed both the aerobic exercise and the resistance exercise regimens as described above. Although aerobic training is the traditionally recommended type of exercise, resistance training has also been shown to improve insulin sensitivity [2,3] and to increase non-oxidative glucose disposal [4], hence for this genetic study the three exercise groups were pooled.…”
Section: Methodsmentioning
confidence: 99%
“…Achievement of optimal glycaemic control is the focus of traditional treatment. Regular exercise, both aerobic and resistance training [2][3][4], results in increased glucose uptake and insulin sensitivity [5,6] and is a primary modality used in the treatment of type 2 diabetic patients [7][8][9]. As with pharmaceutical treatment, large inter-individual responses are observed in exercise training, and are hypothesised to be dependent on genetic background [10].…”
Section: Introductionmentioning
confidence: 99%
“…Previous longer-term resistance training studies alone (17,18,20) or in conjunction with energy restriction (19) have demonstrated significant improvements in insulin action and glucose utilization. One major methodological difference is that metabolic parameters were reassessed 24 h after the last exercise session in those studies, whereas glucose disposal was measured 72 h after resistance training in the current study.…”
Section: Hyperinsulinemic-euglycemic Clampmentioning
confidence: 99%
“…Resistance training (RT) increases insulin sensitivity in older men and women (17)(18)(19)(20). Combining moderate energy restriction with resistance training preserves lean tissue mass and substantially reduces body fat mass (FM) (21,22).…”
mentioning
confidence: 99%